The C-terminal domain of Emi2 conjugated to cell-penetrating peptide activates mouse oocyte - Suzuki, Toru (Frontiers in Cell and Developmental Biology, 2025)
IntroductionThe cell cycle of ovulated oocytes from various animal species, including mice, arrests at the second meiotic metaphase until fertilization. The meiotic cell cycle must be initiated to initiate embryonic development. Besides natural fertilization, several methods have been developed to activate unfertilized oocytes without sperm. These methods aid both animal production and molecular studies on meiotic regulation, oocyte activation, and embryogenesis. This study aimed to develop a method to activate mouse oocytes using a cell-penetrating peptide based on the knowledge that the C-terminal domain of the meiotic protein Emi2 can resume the arrested meiotic cell cycle.MethodsThis study used female B6D2F1 mice to investigate the effects of a cell-penetrating peptide-fused Emi2 peptide on oocyte activation. Second meiotic metaphase oocytes were collected, cultured, and treated with the peptide or strontium chloride. Pronuclear formation, second polar body extrusion, and blastocyst development were assessed, and statistical significance was determined using Fisher’s exact test.ResultsThe cell-penetrating peptide activated zona-intact oocytes in a manner dependent on specific amino acid residues and peptide concentrations, which are critical components for cell membrane penetration. Some oocytes did not survive after the peptide treatment, indicating its cytotoxic effects. It has also been confirmed that oocytes activated using this method can develop to the blastocyst stage.DiscussionThe introduction of peptides or functional amino acid sequences using cell-penetrating peptide or related methods could be an alternative for easily performing functional analyses of the activity of target proteins in oocytes.